2019
DOI: 10.1051/0004-6361/201935496
|View full text |Cite
|
Sign up to set email alerts
|

High gas-to-dust size ratio indicating efficient radial drift in the mm-faint CX Tauri disk

Abstract: The large majority of protoplanetary disks have very compact continuum emission ( 15 AU) at millimeter wavelengths. However, high angular resolution observations that resolve these small disks are still lacking, due to their intrinsically fainter emission compared with large bright disks. In this letter we present 1.3 mm ALMA data of the faint disk (∼ 10 mJy) orbiting the TTauri star CX Tau at a resolution of ∼ 40 mas, ∼ 5 AU in diameter. The millimeter dust disk is compact, with a 68% enclosing flux radius of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 54 publications
11
51
0
Order By: Relevance
“…We find that four of our six disks show a ratio between the R 90,gas and R 90,dust that is very close to or above 4.0, which is similar to the ratio measured in CX Tau (Facchini et al 2019) (ratio of 3.9 ± 0.5 at R 90 ), as compared in Fig. 7.…”
Section: R Gas /R Dust Ratiosupporting
confidence: 86%
See 1 more Smart Citation
“…We find that four of our six disks show a ratio between the R 90,gas and R 90,dust that is very close to or above 4.0, which is similar to the ratio measured in CX Tau (Facchini et al 2019) (ratio of 3.9 ± 0.5 at R 90 ), as compared in Fig. 7.…”
Section: R Gas /R Dust Ratiosupporting
confidence: 86%
“…A more complete sample, which includes more observations of disks around very low and moderate mass stars, and also uniform data sensitivity and analysis are required to confirm if there is a general trend where R gas /R dust increases towards lower stellar masses. (2018) (abbreviated as A+18), CX Tau (Facchini et al 2019), and the targets reported in this paper. For CX Tau, we took the R 90 radii of the dust and gas.…”
Section: R Gas /R Dust Ratiomentioning
confidence: 99%
“…From both Kudo et al 2018;Huélamo et al 2015) this difference is still quite large for UX Tauri A. However, Facchini et al (2019) reported in CX Tauri a large difference of the millimeter dust and gas extents (> 5) and argue that the this could be explained due to a radial drift, and closely matches the predictions of theoretical models. This difference in dust and gas extents is notorious for UX Tauri A, however, it is not clear for UX Tau C because we did not detect the continuum emission.…”
Section: Ux Tauri System (A/c)supporting
confidence: 73%
“…This is a conservative choice in terms of the observed range of values (Isella et al 2016;Ansdell et al 2018;Facchini et al 2019) that mimics the HD 163296ʼs radial behavior of gas and dust. The solids concentration factor ξ is used in conjunction with the mass fraction of condensed material Z i (shown in Figure 2 and described in Section 2.5 and Table 3) to compute the radial distribution of solids…”
Section: Planetesimal Disk and Time Step Of The Simulationsmentioning
confidence: 99%